An Empirical Study of Factors Affecting the Rate of Spam - Miani, Rodrigo Sanches; Oliveira, Danielle; Park, Kil Jin Brandini; Zarpelão, Bruno Bogaz (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2018: Anais do XXXVI Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc.2018.2419, 2018)
Several factors may influence the number of spam received by email users, from user's profile information such as age or nationality to the way the email account is exposed on the Web. We propose a replication study of an experiment conducted more than a decade ago to understand the changes in the dynamics of the business of spam. To that end, using real email addresses created and managed only for the experiment, we simulate four different behavior profiles: i) interaction on social networks, ii) purchase in e-commerce sites, iii) interaction on forums and message boards and iv) use of file sharing tools, and analyze the amount of spam received on those accounts. The results indicate that linking an email account to a social network is the most significant influence on the spam rate.